NATIONAL CULTURE AS A DETERMINANT OF ATTITUDES ABOUT LEADERSHIP STYLES - Vasilic, Nikola G; Brković, Pavle (International Journal of Economic Practice and Policy, 2018)
National culture represents a system of values, assumptions, beliefs, norms and attitudes that members of a nation have towards key issues and problems, which are a representative of the historical past of that nation. Consequently, national culture is an essential determinant of leadership styles, since the assumptions, attitudes and ways in which members of a nation perceive leaders and their behavior depends on which leadership style proves to be the most effective one. The aim of this paper is to determine the significance and type of influence of national culture on the attitudes on transformational and transactional leadership. The main instrument for conducting the research is a questionnaire, which was sent via e-mail to the address of 140 respondents. The results of the multiple regression analysis show that uncertainty avoidance has a significant, as well a negative impact on the attitude of the transformational style of leadership. In the regression model in which the views on transactional leadership depend on the variable, the dimension of collectivism and female values ​​only have statistically significant, negative effects. The remaining tested variables have statistically insignificant effects on the attitudes on leadership styles.